Do Related Party Transactions Affect Firm Value? - Veronica Veren Milenia; Kusuma Indawati Halim (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2026)
Using panel data of 24 firms in the Indonesian property and real estate sector from 2019 to 2023, this study investigates the impact of related party transactions on firm value by emphasizing the influence of firm size and family ownership. Tobin's Q was used in the analyses to measure firm value, with leverage, profitability, and liquidity as control variables. Empirical evidence demonstrates that related party receivables have a significant negative effect on firm value, thus confirming the agency theory. Related party payables, on the other hand, have a positive correlation with firm value, showing the potential as an internal financing mechanism and giving a good signal to the market. Furthermore, firm size has been shown to mitigate the adverse impacts of accounts receivable while magnifying the beneficial effects of accounts payable. Although family-owned businesses extract greater value from accounts payable than non-family-owned enterprises, there is no distinction in accounts receivable between the two. Nonetheless, this study shows that related party transactions are not necessarily harmful for companies. These findings are important for business management, regulators, and investors seeking to consider related party transactions that can increase firm value.